Analisis Kepuasan Mahasiswa Terhadap Pelayanan di Institut Teknologi Telkom Purwokerto - YD Suryaningtiyas; Silvia Van Marshally (Universitas Kristen Indonesia Toraja, 2024)
The research was carrided out considering the importance of maintaining the quality of higher education, especialy of quite tight competition among private universities. One of the quality stadards at the Telkom Institute of Technology Purwokerto is the level of student satisfaction with institut services. This is stated in the ITTP managemet contract with the foundation organization as one of the Key Performance Indicators (KPI). The aim of this research is to find out the level of student satisfaction with the servicces provided by ITTP. Service Quality indicators consist of five aspects: reability, responiveness, assurance, emphaty and tangibles. The population in this study were active students in the even semester 2023-2024 and the number of responets who filled in was 3.848 or almost 80% of the population. Research data was obtaining using a survey system via the website link sai.ittelkom-pwt.ac.id which contains 50 question items. A simple linier regression analysis method was used to analyze the data obtained. The research result show that ITTP student’s satisfaction responses to the services provided include aspects of reability, responiveness, assurance, emphaty and tangibles in the “Good” category with a satisfaction index of 74, 76%. It turned out that the measurement results were not in accordance with the target set “Very Good” or score 80,50%. Because there were still several infrastructure facilities that had not been met such as parking area, open space for discussions or doing assigments and improvements to classroom facilities